Effect of Recharge and Abstraction on Groundwater Levels - Rael Nyakundi; Maurice Nyadawa; John Mwangi (Civil Engineering Journal, 2022)
Groundwater constitutes 99% of all liquid freshwater globally that is available for human use. Groundwater levels in the Nairobi aquifer system (NAS) have been declining over time because of excessive abstraction fueled by increased water demand. This has increased the cost of pumping and drilling boreholes, which is unsustainable. The objective of this study is to determine the effect of recharge and abstraction on groundwater levels using a more realistic approach by estimating recharge using the SWAT model while considering climatic data, soil type, land use/cover, and topography. Recharge obtained from SWAT was applied in MODFLOW to model the groundwater system. Results showed that the average annual recharge was 73 mm, which is about 9.7% of the precipitation. Groundwater levels decreased with an increase in abstraction and a decrease in recharge and vice versa. Groundwater levels will decrease by 76 m by the year 2063 if the abstraction rate is kept constant and the recharge is maintained, and will decrease by 14m by the year 2030 if the trend of abstraction rate continues to increase while recharge is kept constant. The abstraction rate should be regulated according to available recharge and recharge enhanced to avoid possible depletion of groundwater. Doi: 10.28991/CEJ-2022-08-05-05 Full Text: PDF